Investigating the potential of producing alkanes and other fatty acid-derived biofuels using the thermophilic chassis Geobacillus thermoglucosidasius - Habgood, Robert (2018)
Diminishing fossil fuel reserves and the drawbacks of conventional crop-based biofuels has catalysed recent research into the microbial conversion of lignocellulosic biomass into liquid biofuel. Fatty acids represent the most abundant form of reduced carbon chain in nature, and represent the basic building blocks for the creation of a wide-range of advanced biofuels; such as alkanes, fatty alcohols, and fatty acid methyl- and ethyl-esters. It is hoped that the use of a thermophilic platform strain, that is capable of producing fatty acid-derived biofuels at elevated temperatures, will circumvent some of the challenges faced by established mesophilic organisms such as Escherichia coli or Saccharomyces cerevisiae. Here we describe the heterologous expression of an alkane biosynthesis pathway from the thermophilic cyanobacteria Thermosynechococcus elongatus BP-1 in both E. coli and the thermophilic production organism Geobacillus thermoglucosidasius. Alkane biosynthesis in T. elongatus BP-1 is facilitated by two enzymes: fatty acyl-ACP reductase (AAR) and aldehyde deformylating oxygenase (ADO): both of which were found to demonstrate a level of activity in vivo at mesophilic and thermophilic temperatures (30 - 52°C). Expression of an alkane biosynthesis operon in G. thermoglucosidasius NCIMB 11955 resulted in the production of ~100 mg OD-1 L-1 fatty alcohols, and an inconsistent formation of minute amounts of heptadecane. Improved titres of alkane may be achievable through the identification and elimination of competing pathways, and a better understanding of n-alkane biodegradation in G. thermoglucosidasius. However, we recommend the continued pursuit of fatty alcohol production using G. thermoglucosidasius as a host. Elimination of several fatty acid degradation (fad) genes in G. thermoglucosidasius was undertaken with the hope of showing an ability to manipulate the cellular pool of fatty acyl-ACP substrates available to the alkane biosynthesis pathway. The combined elimination of two long-chain-fatty-acid—CoA ligase genes (fadD1 and fadD2) resulted in increased levels of pentadecanoic- and heptadecanoic acid. The heterologous expression of a fatty acyl-ACP thioesterase (FAT) from Clostridium thermocellum and from the Aminicenantes candidate phylum (OP-8) was also undertaken in an attempt to manipulate levels of cellular FFAs, although we postulate that observation of a differential phenotype requires the development of a strain completely defunct of long-chain-fatty-acid—CoA ligase activity. Fatty acid metabolism in G. thermoglucosidasius represents a complex myriad of multiple genes that are subject to strong homeostasis. Nevertheless, we present evidence that genetic manipulations of G. thermoglucosidasius are sufficient to bring about changes in the fatty acid profile of cells, and encourage the further genetic characterization of fatty acid metabolism in the organism through targeted gene deletions, with the hope of producing an improved platform strain for fatty alcohol and alkane biosynthesis at thermophilic temperatures.